Sociocultural Factor of Influence on the Formation of Ideas of the Scientific Management of Labour in the Works of Aleksei Gastev - I. V. Dvoluchanskii (Управленческое консультирование)
This article considers the change of Aleksei Gastev’s ideas on the scientific management of labour (SML) — one of the first scientific schools of management in the history of managerial thought of the Soviet period. This scientific school of management was created in the 1920s. This period is characterized by active industrial growth, which led to the migration of people from rural areas to the industrial centers of the country. Alexei Gastev, as an ideologist of the SML, proposed to solve this problem through the creation of a new culture. The following research aimis chosen in order to study this historical interval: to identify the specifics of the process of forming the new culture in the ideas of Aleksei Gastev in the socio-cultural context of the 1920s. The object of the study is materials containing Aleksei Gastev’s ideas on labour of scientific management in the period from 1920 to 1930, and the subject of the study is the process of changing of Aleksei Gastev’s ideas of scientific management labour. The article substantiates the connection between the socio-cultural situation of workers in the 1920s and the formation of the ideas of scientific management labour. The characteristic feature of the ideas of scientific management labour, aimed at the formation of the new culture of labour, is revealed. A characteristic of the practices of introducing the new culture of labour formed by self-colonization and discipline of the body is given.